The Relationship Between Phlebotomists' Knowledge, Attitudes, and Behaviors Regarding Venous Blood Specimen Collection and Handling with Laboratory Specimen Quality at RSUD X - Aeni, Suci Rizki Nurul; Ramadianti, Dwi Anjani; Andriani, Novi; Haruniati, Zakiyah Aulia (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Pre-analytical errors contribute to approximately 70% of all laboratory testing errors, including errors in blood specimen collection and handling. Improper blood specimen collection and handling procedures can lead to inaccurate test results, resulting in misinterpretation of laboratory test results. Crossmatching, a procedure to match patient and donor blood prior to transfusion, is a crucial step in this process. However, the urgent need for blood transfusions in thalassemia patients often necessitates expedited crossmatching, sometimes even omitting the incubation phase. This accelerated process may compromise the accuracy of the crossmatch results. To determine the relationship between phlebotomists' knowledge, attitudes, and behaviors regarding blood specimen collection and handling with the quality of venous blood specimens in the laboratory of RSUD X. To evaluate the impact of incubation on gel test crossmatch results in thalassemia patients at RSUD Jampangkulon.This was an analytical observational study using a questionnaire instrument. The research sample consisted of 126 nurses and 14 medical laboratory technicians at RSUD X. The sampling technique used was disproportionate stratified random sampling. Data analysis used the Chi-square test. A quasi-experimental design with a one-group pre-test and post-test design was adopted for this study. Gel test crossmatching was employed to analyze the samples, and the Wilcoxon signed-rank test was conducted to assess for statistically significant differences. There was a relationship between phlebotomists' knowledge of blood specimen collection and handling and the quality of laboratory specimens (p-value 0.001). There was no relationship between phlebotomists' attitudes toward blood specimen collection and handling and the quality of laboratory specimens (p-value 0.682). There was no relationship between phlebotomists' behavior in blood specimen collection and handling and the quality of laboratory specimens (p-value 0.494). Both incubated and non-incubated crossmatch tests yielded identical results for major, minor, and autocontrol compatibility in 11 thalassemia patient samples. However, 14 samples demonstrated incompatibility in the minor and autocontrol categories. Wilcoxon signed-rank test results showed a p-value of 0.000 (p<0.05) for the incubated group and an asymptotic significance (2-tailed) of 1.000 (>0.05). Similarly, the non-incubated group exhibited a p-value of 0.000 (p<0.05) and an asymptotic significance (2-tailed) of 1.000 (>0.05). There is a significant relationship between phlebotomists' knowledge of blood specimen collection and handling and the quality of laboratory specimens at RSUD X. There is no relationship between phlebotomists' attitudes and behaviors regarding blood specimen collection and handling and the quality of laboratory specimens at RSUD X. There was no significant difference in the results between the incubated and non-incubated samples of thalassemia patients.